Physicochemical quality parameters of the generic drug hydrochlorothiazide in relation to the reference drug Clorana® - Trindade, Jéssica Aparecida Silva (2021)
This study aimed to compare the physical-chemical parameters of quality of the generic drug hydrochlorothiazide 25 mg in relation to the reference drug Clorana®. The following tests were performed: determination of average weight, identification, hardness, friability, disintegration, dissolution and dosing. All tests showed satisfactory results. In determining the average weight, the results obtained for both drugs showed little variation. In the identification test, the sample readings were in agreement with the standard. The hardness test was informative. The resistance to friction and impact of the tablets was within the parameters, so the friability was satisfactory. The hydrochlorothiazide tablets disintegrated in a longer time than those of Chlorana®, but within the established. Both drugs were dissolved within the precise time. In the dosing test, the content obtained was within the conformities. In view of the results of the tests of the physical-chemical tests, the study proved that the drugs are within the quality parameters and certified the safety in physical-chemical terms of the use of the generic drug tested in the treatment of Systemic Arterial Hypertension.